ANALISIS PUTUSAN BEBAS DALAM KASASI YANG DIAJUKAN TERDAKWA YANG DISEBABKAN KESALAHAN PENYIDIK DALAM PENANGKAPAN - Danar Harryasdito; Itok Dwi Kurniawan (Verstek, 2025)
This research describes and examines the problems, firstly, analyzing police investigators as witnesses in narcotics crimes and the validity of witness statements by police investigators in narcotics crimes, secondly, in order to decide criminal cases two criteria must be met, namely supported by at least lack of two pieces of evidence, and the judge is convinced that the defendant committed the crime. In the event that the judge does not obtain a conviction, the judge is obliged to give a decision that is favorable to the accused (in dubio pro reo). However, in practice this principle is often not implemented. This research uses normative legal research methods with a statutory approach and a case approach. The legal materials used are primary legal materials, secondary legal materials and analyzed normatively descriptively. The research results show, first, that there are no specific and strict provisions in the criminal procedural law that either allow or prohibit police investigators from being witnesses. Investigators can be witnesses in drug crimes as long as they meet the qualifications and are not included in the group of people who are exempt from the obligation to testify in trials, where Article 185 paragraph (6) of the Criminal Procedure Code requires witness statements to be "free, neutral, objective and honest". Second, the urgency of the in dubio pro rio principle in criminal procedural law in Indonesia is to prevent wrongful convictions from occurring, because if wrongful convictions occur, it is the same as eliminating human rights, namely the right to liberty and the right to life.